GSDMD is a novel predictive biomarker for immunotherapy response: in the pan-cancer and single cell landscapes - Huang, Li Juan; Chen, Feng; Chen, Lin; Zhan, Shi Tong; Liu, Ming Min; Xiang, Jiang Dong; Zhang, Qin Yi; Yang, Ye (Frontiers in Immunology, 2025)
BackgroundGasdermin D (GSDMD), a key executor of pyroptosis, has been implicated in modulating the tumor immune microenvironment. However, its role as a predictive biomarker for immunotherapy response remains unclear.MethodsWe conducted a pan-cancer analysis of GSDMD expression across TCGA datasets and investigated its association with tumor mutational burden (TMB), microsatellite instability (MSI), and mismatch repair (MMR) status. Immunological relevance was further assessed by correlating GSDMD expression with immune cell infiltration and immune checkpoint gene signatures. We performed single-cell RNA sequencing analysis to investigate the immune cell populations and immunological pathways associated with GSDMD expression. Finally, organoid-based functional assays confirmed that Poly ADP-ribose polymerase inhibitors (PARPi) exert antitumor effects at least in part by enhancing GSDMD-mediated pyroptosis.ResultsGSDMD was found to be aberrantly expressed in multiple tumor types and positively correlated with TMB, MSI, and immune checkpoint expression. High GSDMD expression was associated with increased infiltration of pro-inflammatory immune cells. In organoid models, GSDMD expression influenced sensitivity to PARPi, suggesting a potential role in shaping the immune-responsive phenotype.ConclusionOur findings highlight GSDMD as a potential biomarker for predicting immunotherapy response and as a modulator of tumor-immune interactions. These results provide a foundation for future studies exploring GSDMD-targeted strategies to enhance immunotherapeutic efficacy.